Multi-dimensional poverty and sustainable human development in Iraq - مسلم, حمدية شاكر (Journal of Economics and Administrative Sciences, 2014)
The problem of poverty and deprivation constitute a humanitarian tragedy and its continuation may threaten the political achievements reached by the State. Iraq, in particular, and although he is one of the very rich countries due to availability of huge economic wealth, poverty indicators are still high. In addition, the main factor in the decline in the standard of living due to the weakness of the government's performance in the delivery of public services of water, electricity and sanitation. Thus, the guide for human development has been addressed which express the achievements that the state can be achieved both on a physical level or on the human level, so in order to put appropriate strategies and policies aimed at eliminating this phenomenon or mitigate the severity. And includes the most important indicators used to measure the finale indicators of deprivation (multi-dimensional poverty including health, education, housing and infrastructure), The study found the most effective dimensions on poverty and where it is most concentrated in governments and the status quo of poverty for a family of Iraq in light of the services provided by the state. Achieving sustainable development by the government requires performing new roles in the fields of ​​coordination, regulation, legislation and support, so as to create the necessary conditions and fertile ground for the work of civil society organizations, as well as the government and the private sector due to its vital role in the formulation and implementation of many complementary programs and goals of the government policies and programs and  the private sector, not to mention the economic programs such as eradicating poverty, employment and others. .